Validation of flank-to-flank allometric equations in predicting weight of lactating sows and lactation weight change - Sulabo, R.C.; Tokach, Michael D.; Wiedmann, E.J.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The objectives of this study were to validate the use of flank-to-flank measurement in predicting weight of lactating sows and to determine the accuracy of the developed models in estimating lactation weight change. A total of 70 lactating sows (PIC Line 1050) were used in this study. Flank-to-flank measurement and body weight were measured on each individual sow after farrowing and at weaning. Flank-to-flank measurement and weight of lactating sows was positively correlated (R2 = 0.61; P<.0001) with the following equation: BW0.33, kg = 0.0371 x Flank-to-flank (cm) + 2.161. Weights of sows post-farrowing and at weaning were lower (P<0.03) when predicted with the previous allometric model developed from growing pigs and sows than their actual weights or weights predicted using the lactating sow model. Likewise, absolute residuals for post-farrowing and weaning weights using a previous allometric model developed from growing pigs and gestating sows were greater (P<0.02) than those of the lactating sow model. There were no differences (P<0.89) between the predicted weights using the lactating sow model and their actual weights. There also were no differences between the actual average weight loss (P<0.14) and the predicted loss using the lactating sow model. Using the model previously developed with growing pigs and gestating sows resulted in 15.5 lb (P<0.007) greater than the actual average weight loss. In conclusion, flank-to-flank measurement can be used as a predictor of weight of lactating sows, with the relationship having less accuracy than those used for growing-finishing pigs, gestating sows, and boars. The pig allometric equation cannot be used to estimate weights of lactating sows and lactation weight change. The developed lactating sow model was more appropriate in estimating weights and weight loss at the herd level, but needs to be validated on other sows before use can be recommended.
Keywords: Swine; Lactating sows; Flank-to-flank; allometric equations; Weight